Palliative Management of Malignant Bowel Obstruction in Terminally Ill Patient - Thaker, Darshit A (Medknow Publications, 2010)
Mr. P was a 57-year-old man who presented with symptoms of bowel obstruction in the setting of a known metastatic pancreatic cancer. Diagnosis of malignant bowel obstruction was made clinically and radiologically and he was treated conservatively (non-operatively)with octreotide, metoclopromide and dexamethasone, which provided good control over symptoms and allowed him to have quality time with family until he died few weeks later with liver failure. Bowel obstruction in patients with abdominal malignancy requires careful assessment. The patient and family should always be involved in decision making. The ultimate goals of palliative care (symptom management, quality of life and dignity of death) should never be forgotten during decision making for any patient.